Analysis of the Duties and Functions of the Village Consultative Body (BPD) of Pengujan Village, Teluk Bintan District, Bintan Regency - Fauzan Lidra Ramadhani; Nabil Daffa Rizky (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2026)
This study aims to analyze the implementation of the duties and functions of the Village Consultative Body (BPD) of Pengujan Village in village governance based on Regulation of the Minister of Home Affairs Number 110 of 2016. This research employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews, observation, and documentation involving the village head, BPD members, village officials, and community representatives. The findings indicate that the BPD of Pengujan Village has normatively performed its main functions, including absorbing community aspirations, organizing village deliberations, discussing village regulations, and supervising the performance of the village government. However, the effectiveness of these functions remains constrained by several factors, such as limited human resource capacity, unequal community participation, and a gap between formal procedures and substantive practices. Supervision conducted by the BPD tends to be administrative in nature, while public participation in the village legislative process has not been fully inclusive. This study concludes that strengthening the role of the BPD requires not only regulatory compliance but also improvements in institutional capacity, transparency, and more substantive community participation mechanisms.